Hubungan Budaya Organisasi Dengan Kualitas Pelayanan Kesehatan Di Puskesmas Bajo Barat Kabupaten Luwu (Window of Public Health Journal, 2025)
The Bajo Barat Community Health Center faces multidimensional problems that include aspects of service, justice, human resource management, and infrastructure. This condition risks reducing the overall quality of health services, increasing the number of public complaints, and hampering efforts to improve public health in the region. Therefore, a comprehensive evaluation and systemic improvements were carried out as a strategic step to improve the quality of services and public trust in health institutions. This study used a quantitative research method with a cross-sectional design. The population in this study consisted of all health workers in the Bajo Barat Community Health Center's work area, totaling 75 individuals. The results of the chi-square test showed that five variables—self-awareness, aggressiveness, personality, performance, and team orientation- had a significant relationship with the quality of health services, with p-values less than 0.05, indicating these factors are statistically significant. Clarifying the meaning of p-values helps stakeholders understand which variables truly impact service quality and where to focus improvement efforts.